Kajian Studi Hermeneutis tentang Jatuhnya Talaq dalam Prespektif Fikih dan Undang-Undang No 1 Tahun 1974 - Hafid Hafid; Hairul Ulum (Qolamuna : Jurnal Studi Islam, 2019)
This article discusses the Hermeneutical Study of the Fall of Divorce in the Jurisprudence Perspective and Law No. 1 of 1974. The results of research on the issue of the divorce according to the perspective of Jurisprudence and Law No. 1 of 1974, then concluded as follows; First, the fall of divorce in the view of Jurisprudence and Law No. 1 of 1974 descriptively hermeneutical, is a khilafiyah issue of ijtihadiyah because it is dhanni. Divorce should be before the Religious Courts by Law No.1 of 1974 not containing significant text, because divorce does not have to be done before the court. Secondly, there is a clear fall in the perspective of fiqh and Law no. 1 of 1974, is more influenced by the device that its formation. Keywords; Hermeneutis, Talaq, Fiqh and the 1974 Law